A Study of the Recidivism Rate of First Offenders at Louisiana Correctional and Industrial School Who Completed Vocational Training Through L.C.I.S./Sowela Institute - LeBleu, Harold J. (1984)
T h e p i.i. r p 0 s e o f' t h e s t 'J. d y w a. •=• t o d e t e r rn i n & i t 1 n m a t e s r e 1 e a. s e d +' r c> rn i_ o u i s i a n a C o r r e c t i o n a. 1 a n d Industrial School who completed a v o c a t i o n a 1 t r a i n i n 9 p r 0 9 r a rn t h r 0 u. 9 h L • C • I • S ■ S 0 w e l a T e c h n i c a 1 I n s t i t u t 0 h a d a 1 o w e r r a t e o f 0 f r e c i d i v i s rn t h a n t h 0 s e w h 0 d i d n ot c 0 rn p 1 e t e t r a i ti i ti 9 j u. s i n 9 a 9 e a s a v a r i a b 1 e ■ The population for this study consisted of a r a n d o rn s a rn pie o f' 99 i n rn a t es r e 1 e a se d i n t o t h e 9 e n e r a 1 p o p u 1 a t i 0 n 0 f' L o u. i s i a n a p r i o r t o 1 9 S 3- T h e s e s u b ,i ec t s o 1 a n t a r i 1 y c o rn p 1 e t e d oc a. t i o n a 1 t r a 1 n i n9 i n in e 1 d i. n 9 ? a u t o m e c h a n i c s ? o r t< 0 d y a n d f e n d e r repair betweeri the years 1376-1982 • The control s a rn p 1 e c o ns i s t e d 0f 101 i n rn a tes selects d r a n d o rn 1 y + rom the tot a1 p r i so n p op u 1 a t i on at L • C ■ I • S ■ dur i n9 19,-b- and who were released into the general P o p u 1 a t i o n o t L o u. i s i a ti a p r i o r t o 1983. Three years were a 110wed f'0r the reci d ivism period- R e c i d i v i s rn w a s 0 p e r a t i 0 n a 1 i z e d a s r e t u r n 1 n 9 t o p r i s 0 fi o r o b t a i n i ti 9 a n e w f e 1 o n y >_ h a r 9 e ? v e r i f' i e d fc> y Loij. i s i a na Dep- a.r t rne r 11 of Correc t i o ns dat a. a. nd the FBI c 0 rn p u t e r s y s t e rn. C h i - s q u. a re t e s t s were p e r f' 0 r m e d t o deter rn i n e the re 1 a t i 0 n s h i. p b e t w e e n t r a i n i n 9 a n d r ec i d i v i srn , t he re 1 -at j r. nship be twee n a•?e a nd completing t r a i n i n y > and between age at release and recidivism- T h e m e d i a n a 9 e o f' t h e p o p u 1 a t1 o n w a s 2 4.3 9 years- The younger subgroup ranged in age + row ly y e a. r s t0 2 4 y e a r s ■ The aide r s u. b 9 r o u. p rn e rn b e r s w ere greater than 25 years old. Treatment alone was not significant in reducing recidivism- Of all prisoners c o m pie t i n 9 v o c a t i o n a 1 t r a i n i n 9 6 3.3 '< w ere o 1 d e r t h a n 2 5 y e a r s • ft 9 e w a s s i 9 n i f i c a n t i n c o m p 1 e t i n 9 t r e a t m e n t 1.1.1 i t h a chi s q V. a re sc o r e o ft 3 • 3 3 ? a t t h e • ft 5 1 e v e 1 o f s i 9n i ft i ca nce• Age a t t i rne oft re 1 ea se wa s r e 1. a t o d to reduced recidivism. This variable was significant w i t h a ch i sq u.ar e va ]. ue of 5 • 3 5 . a t the • ft 2 1 e• e 1 oft s i9 n ift icanc e. Prison e r s ove r 25 y ears of a g e had a recidivism rate of £2*4 '. while those prisoners who w ere y ou. n9e r h a d a r ec i d i v 1 s m r a t e o ft 4ft ■ 2. • The combined effect of treatment and age was significant i n r e duc 1 n9 r ec i d i v ism, w i t h a chi- s q u. ar e v a 1 u. e o ft a t the ■ d 5 1 e e 1 o ft s i 9 n i ft 1 c a n c e